2010
DOI: 10.1523/jneurosci.4289-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Ameliorates Nucleus Accumbens Phase-Signaling Dysfunction in a Genetic Mouse Model of Mania

Abstract: Polymorphisms in circadian genes such as CLOCK convey risk for bipolar disorder. While studies have begun to elucidate the molecular mechanism whereby disruption of Clock alters cellular function within mesolimbic brain regions, little remains known about how these changes alter gross neural circuit function and generate mania-like behaviors in Clock-Δ19 mice. Here we show that the phasic entrainment of nucleus accumbens (NAC) low-gamma (30–55Hz) oscillations to delta (1–4Hz) oscillations is negatively correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 44 publications
4
66
0
Order By: Relevance
“…The most thorough examination of this frequency band in the behaving rodent may be that of Fujisawa and Buzsáki (2011), who found that coherence between 2 and 5 Hz increased between the ventral tegmental area (VTA) and prelimbic cortex during an odor-to-place matching task, and that this oscillation was phase-coupled with theta in the dorsal hippocampus. This report extended previous observations that VTA neurons often fire action potentials at regular intervals of 4 Hz (Hyland et al, 2002;Paladini and Tepper, 1999;Bayer et al, 2007;Dzirasa et al, 2010;Kobayashi and Schultz, 2008). Hippocampal-prefrontal coherence in the 4 Hz band can also increase when dopamine is injection directly into the prefrontal cortex (Benchenane et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…The most thorough examination of this frequency band in the behaving rodent may be that of Fujisawa and Buzsáki (2011), who found that coherence between 2 and 5 Hz increased between the ventral tegmental area (VTA) and prelimbic cortex during an odor-to-place matching task, and that this oscillation was phase-coupled with theta in the dorsal hippocampus. This report extended previous observations that VTA neurons often fire action potentials at regular intervals of 4 Hz (Hyland et al, 2002;Paladini and Tepper, 1999;Bayer et al, 2007;Dzirasa et al, 2010;Kobayashi and Schultz, 2008). Hippocampal-prefrontal coherence in the 4 Hz band can also increase when dopamine is injection directly into the prefrontal cortex (Benchenane et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…What is clear from all of these studies is that anxiety-related behavior and depressionrelated behavior are regulated by separate mechanisms. Recently, we found that the ClockD19 mice have a defect in the phasic entrainment of d and g oscillations in the NAc neurons, which can be rescued by chronic lithium treatment (Dzirasa et al, 2010). It is very likely that it is not merely the increase or decrease in firing rates within the VTA-NAc circuit that is important in regulating mood, but the patterns of firing, oscillations, and coherence between and within structures is what dictates the behavioral-and moodrelated outputs.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, growing evidence has raised the possibility of striatal dysfunction associated with ADHD and autism (Durston et al 2003;Lou et al 2004;Di Martino et al 2011;Peca et al 2011). Interestingly, a notable number of mouse models for neuropsychiatric disorders share a common phenotype of elevated locomotor activity (Bolivar et al 2004;Welch et al 2007;Dzirasa et al 2010;Penagarikano et al 2011;Won et al 2012). A study in mice deficient of contactin associated protein-like 2 (CNTNAP2) reported that hyperactivity and perseveration could be rescued by risperidone, a dopamine D 2 receptor agonist, while social deficits remained impaired.…”
Section: The Modulation Of Excitatory and Inhibitory Balance In Locommentioning
confidence: 99%